Highly sensitive acetone sensors based on flame-spray-made La2O3-doped SnO2nanoparticulate thick films - N. Tammanoon (2018)
© 2018 Elsevier B.V. In the present work, flame-spray-made La 2 O 3 -doped SnO 2 nanoparticles with 0.1−2 wt% La contents were systematically studied for acetone detection. The particle and sensing film properties were characterized by X-ray diffraction, nitrogen adsorption, electron microscopy, energy dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy. The sensing films were tested towards 0.1–400 ppm acetone at operating temperatures ranging from 150 to 400 °C in dry air. Gas-sensing results demonstrated that the SnO 2 sensing film with the optimal La content of 0.5 wt% exhibited a very high response of 3626 toward 400 ppm acetone with a short response time of 2.8 s at the optimal operating temperature of 350 °C. Moreover, the sensors displayed high acetone selectivity against SO 2 , H 2 S, NO 2 , C 6 H 6 , C 7 H 8 , C 8 H 10 and CH 2 O. Therefore, the La 2 O 3 -doped SnO 2 sensors are promising for sensitive and selective detections of acetone at low concentrations.